UNDERSTANDING POLITICAL ISSUES THROUGH SOCIAL ACTORS REPRESENTATION: - Cut Nina Sausina; Dwi Indarti (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
Critical Discourse Analysis attempts to investigate social, political, historical and environmental issues by analyzing linguistic aspects and resources. This paper aims to examine the strategies used by journalists of tempo.co and CNN Indonesia in delivering the Governor of NTT’s school policy. Two research questions are formulated: (1) How the social actors are described in the news of Governor NTT’s policy publish in tempo.co and cnnindonesia.com. (2) What strategies used by tempo.co and cnnindonesia.com in describing the social actors of Governor NTT’s policy news. The results of the study indicate that the social actors are described in the news of Governor NTT’s policy publish in tempo.co and cnnindonesia.com by clearly mentioned the actors who responsible for the entry school policy. This educates the readers about the policy. Even though the actors are clearly mentioned, there is no tendency to marginalize them, especially Governor of NTT. By covering all person in charge, the readers are presented proportional news. Strategies used by tempo.co and cnnindonesia.com in describing the social actors of Governor NTT’s policy news is only inclusion strategy. Meanwhile, exclusion strategy is not detected in both news by tempo.co and CNN Indonesia.